Żywotność praktyk magicznych na przykładzie sposobów ochrony dzieci przed urokiem (przygotowano z materiałów „Polskiego Atlasu Etnograficznego”) - Pieńczak, Agnieszka (Studia Etnologiczne i Antropologiczne, 2011)
The article presents the results of the research works of the Polish Ethnographic Atlas, presenting the topicality of magic practices concerning the ways of preventing children from spell. It constitutes an attempt of a cartographic analysis of data collected in the 1970s in 338 research points situated Poland wide. Atlas studies showed that the communities under investigation knew and practised different ways of preventing children from spell. These involve for example practices connected with using of elements in an intensive colour, isolative practices (ban on showing a child to strangers and covering it with cloth), practices concerned with turning the clothes inside out, practices combined with using impurity (spitting), practices connected with using sacred objects and votive gestures. The images on maps point to the relict nature of analysed magic practices on the one hand, and their former popularity in Poland (scattered and edged scope prove it). The maps show that some practices were maintained longer in the eastern and south-eastern Poland than in other areas. The very territory is often defined as the most conservative in terms of the traditional folk culture.